The one- and two-handed backhands in tennis - Reid, M.; Elliott, B. (Sports Biomechanics, 2002)
The study investigated differences in the one- (SH) and two-handed (DH) backhands when hit flat, across-court (AC) and down-the-line (DL), and with heavy topspin DL (TDL). The ability to disguise each of these backhands when hitting the above strokes was also assessed. Eighteen college-level male tennis players, identified as having a high performance topspin SH (n = 6) or DH (n = 12) backhand drive, participated in the study. Players were required to hit three AC, DL and TDL backhands from the baseline with their preferred technique, while being filmed with two high-speed video cameras operating at 200 Hz. The highest horizontal velocity backhand for each stroke was analysed. Results indicated that the sequential coordination of five body segments (hips, shoulder, upper arm, forearm, and hand/racquet rotations) was required for the execution of the SH stroke. The same number of segments were generally coordinated in the DH stroke (hips, shoulders, and varying degrees of upper arm and forearm rotations followed by hand/racquet movement). Mature players produced comparable racquet horizontal velocities 0.005 s prior to impact using either the SH or DH backhand technique. The SH backhand was characterised by a more rotated shoulder alignment than the DH stroke (SH: 119.1°; DH: 83.4°) at the completion of the backswing. At impact the ball was impacted further in front (SH: 0.59 m; DH: 0.40 m) and a similar distance to the side of the body (SH: 0.75 m; DH: 0.70 m). Players using the DH backhand technique delayed the horizontal acceleration of the racquet towards the ball (SH: 0.13 s; DH: 0.08 s prior to impact) and thus were capable of displaying a similar hitting motion closer to impact than players with a SH technique.